Association between ultraviolet radiation exposure dose and cataract in Han people living in China and Taiwan: A cross-sectional study - Miyashita, Hisanori (PLoS One, 2019)
PURPOSE: We investigated associations between ocular ultraviolet (UV) radiation exposure dose and cataract opacities among Han people living in China and Taiwan, to assess the effects of UV exposure intensity. METHODS: This cross-sectional study included Han people aged ≥40 years (1,801 individuals, 450 in Sanya, 636 in Taiyuan, and 715 in Taichung) as subjects who completed a questionnaire including items about diabetes, smoking, steroid use, work history, and time spent outdoors, and underwent an ophthalmic examination. Right eye axial length was measured using A-mode ultrasonography or IOLMaster. Slit-lamp imaging under maximum mydriasis was used to classify cataracts into three major types [cortical (COR), nuclear (NUC), and posterior subcapsular cataracts (PSC)] and two subtypes [retrodots (RD) and waterclefts (WC)] by one ophthalmologist. COR was divided into opacity presence (CEN+) or absence (CEN-) in the central 3-mm diameter area of the pupil. COR was also subdivided into three groups according to opacity shape: axle-shaped opacity concomitant with WC, wedge-shaped opacity around the pupil to the eye center, and ring-shaped opacity in the lens equator along the pupillary margin. The cumulative ocular UV exposure (COUV) was calculated. A logistic regression analysis was used for multivariate analysis. RESULTS: Cataract odds ratios in high COUV eyes were 5.35 for NUC, 1.87 for PSC, and 1.35 for RD. In eyes with WC, risk of COR ring-shaped opacity significantly increased but that of wedge-shaped opacity (CEN+) significantly decreased. In eyes without WC, risk of COR axle-shaped opacity (CEN–) and ring-shaped opacity significantly increased but that of wedge-shaped opacity (CEN+) significantly decreased. CONCLUSIONS: Increased COUV level among Han people may be a risk factor for the development of nuclear cataracts, PSC, retrodots and ring-shaped cortical cataract. Risk of ocular UV exposure for cortical cataract may differ by opacity shape.